A Phenomenological Study on the Experiences of Nursing Students’ Hand-Washing Education Volunteer - Kim, Yun-Jeng; Cho, Eui-Young (韓國컴퓨터情報學會論文誌, 2022)
The purpose of this study is to investigate the meaning and essence of nursing students' experience of handwashing education volunteer program. There were 10 students who participated in the handwashing education service, and data collection was conducted for two months from October to November 2021, and three focus groups were formed and interviewed. Data were analyzed by Colaizz's phenomenological research method. As a result of the study, 3 themes and 10 sub-themes were derived. The three themes were 'personal development', 'self-esteem as a pre-nursing nurse', and 'knowing the meaning of service'. Nursing students learned the meaning of service through handwashing education service, and it was found that they could experience their own inner maturity. Nursing students could see that it was a time to learn the true meaning of service through handwashing education volunteering. The results of this study provided an understanding of the educational service of nursing college students, which can be applied to the diversification of educational service programs. 본 연구의 목적은 간호대학생의 손씻기 교육 봉사 활동을 경험한 그 의미와 본질을 파악하기 위한 질적 연구이다. 손씻기 교육 봉사에 참여한 학생은 10명이며, 자료수집은 2021년 10월부터 11월 까지 2개월 실시하였으며, 3개의 포커스 그룹을 구성하여 면담을 진행하였다. 면담자료는 Colaizzi의 현상학적 연구방법으로 분석하였다. 연구 결과 3개의 주제와 10개의 하부주제로 도출되었다. 3개의 주제는 '개인의 발전', '예비 간호사로서 자부심', '봉사의 의미를 알아감'등으로 나타났다. 간호대학생들은 손씻기 교육 봉사를 통해 봉사의 의미를 알게되었으며, 본인의 내적 성숙을 경험할 수 있는 것으로 나타났다. 간호대학생들은 손씻기 교육봉사를 통해 봉사의 참된 의미를 알아가는 시간이었음을 알 수 있었다. 본 연구 결과 간호 대학생의 교육 봉사에 대한 이해를 제공하였으며, 이는 교육 봉사 프로그램의 다양화에 적용할 수 있을 것이다.